2016
DOI: 10.3758/s13421-016-0640-9
|View full text |Cite
|
Sign up to set email alerts
|

Two scenes or not two scenes: The effects of stimulus repetition and view-similarity on scene categorization from brief displays

Abstract: Previous research suggests that understanding the gist of a scene relies on global structural cues that enable rapid scene categorization. This study used a repetition blindness (RB) paradigm to interrogate the nature of the scene representations used in such rapid categorization. When stimuli are repeated in a rapid serial visual presentation (RSVP) sequence (~10 items/ sec), the second occurrence of the repeated item frequently goes unnoticed, a phenomenon that is attributed to a failure to consolidate two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
(68 reference statements)
1
1
0
Order By: Relevance
“…First, GIST and pixel similarity reflect image representations from separate levels of scene processing and features from both of these representations are used to classify incoming stimuli. This is consistent with numerous accounts of visual scene processing that posit that gist representations are extracted early on in the processing stream and more local scene details are processed later (Hochstein & Ahissar, 2002;Oliva & Torralba, 2001; but see Goldzieher, Andrews, & Harris, 2016). Alternatively, GIST and pixel similarity could capture unique aspects of the same representation of scenes such that the feature sets that compose exemplar-level scene representations reflect some combination of image properties that both pixel and GIST similarity partially capture.…”
Section: Discussionsupporting
confidence: 81%
“…First, GIST and pixel similarity reflect image representations from separate levels of scene processing and features from both of these representations are used to classify incoming stimuli. This is consistent with numerous accounts of visual scene processing that posit that gist representations are extracted early on in the processing stream and more local scene details are processed later (Hochstein & Ahissar, 2002;Oliva & Torralba, 2001; but see Goldzieher, Andrews, & Harris, 2016). Alternatively, GIST and pixel similarity could capture unique aspects of the same representation of scenes such that the feature sets that compose exemplar-level scene representations reflect some combination of image properties that both pixel and GIST similarity partially capture.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, I. M. Harris et al (2012) found RB for pictures of nonmanipulable objects, but not for pictures of manipulable objects (e.g., tools and other objects associated with specific motor acts); in contrast, word versions of both classes of objects yielded robust RB. This finding suggests that identification of objects from pictures may be influenced by a range of cognitive factors that can modulate susceptibility to RB (see also Goldzieher et al, 2017, for a failure to see RB for pictures of natural scenes). However, from these previous studies, it is difficult to know whether the differences in the presence and strength of the RB phenomenon are due to differences in stimulus format (pictures vs. words), or whether they arise from idiosyncratic differences between the stimulus sets and task requirements of different studies.…”
mentioning
confidence: 91%